Antimicrobial activity of the extracts from the Sea buckthorn berries (Hippophae rhamnoides L.) against bacteria of the genus Arcobacter - Kučerová, Simona; Šilha, David; Vytřasová, Jarmila; Švecová, Blanka (Československá společnost mikrobiologická, 2016)
The number of multiresistant strains of bacteria has been increasing rapidly in the last few years. Same can be said for arcobacters, where the resistance against some common antibiotics has been proven. Bacteria of the genus Arcobacter can be a cause of unpleasant diseases not only for animals but also for humans. Therefore their existence in food has to be eliminated. The aim of this project was to test the survival of these microorganisms in the presence of the extracts from sea buckthorn berries. The results of this study show that the sea buckthorn has a bright future as an antimicrobial agent against bacteria of the genus Arcobacter.
Antimikrobiální aktivita rakytníkového extraktu (Hippophae rhamnoides L.) proti bakteriím rodu Arcobacter
Keywords: sea buckthorn; antimicrobial effect; Arcobacter spp.; natural extract; rakytník; antimikrobiální vliv; Arcobacter spp.; přírodní extrakt